Menara KPJ Healthcare, Jalan Tun Razak, Kuala Lumpur / Muhammad Zul Farhan Muhammad Zulkifli ... [et al.] - Muhammad Zul Farhan, Muhammad Zulkifli; Amir Fauzi, Rosli; Muhamad Akram, Hashim; Nur’ain Syazana, Che Zakaria; Khairun Nisa’, Md Khir (2019)
This research report will look into the details of property of Menara KPJ Healthcare, Jalan Tun Razak, Kuala Lumpur. This report includes, the property background, organizational maintenance management, maintenance policy, planning and programme, building design and technology, building condition assessment, maintenance strategy, legal aspect, and financial maintenance management through interview with building’s maintenance management team and research. A conclusion of the technologies and maintenance management will be generated through our understanding of these services in regards to the building requirement as well as other relevant rules and regulations.